The Role Of Halal Labeling, Brand Image, And Brand Trust On Repurchase Decisions On Mixue Products In Surakarta - Nais Irawati; Kussudyarsana (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The aim of this research is to investigate how mixue product repurchase decisions in Surakarta are influenced by brand trust, brand image, and halal labeling. This research used a quantitative approach. The population under consideration was the residents of Surakarta. In this study, purposeful sampling was used, and 151 respondents in total fulfilled the predetermined criteria. The study's primary data source was primary data, which was gathered using a questionnaire. The results of this study's analysis demonstrate that halal labeling, brand image, and brand trust all have a favorable and significant impact on consumers' decisions to repurchase.